Effects of test duration on pressure distribution, pelvic stability, and subjective perception in laboratory investigations for evaluating bicycle saddles and seat pads - Schwanitz, S.; Richter, S.; Michel, F. I. (Journal of Science and Cycling, 2023)
The aim of this study was to investigate the consistency of typical evaluation characteristics used to assess seating systems in cycling for both male and female cyclists, over a ride time of up to 60 minutes. Pressure distribution, pelvic stability, and subjective perception were measured in a laboratory test using a stationary bicycle. Results showed that mean pressure load increased with the duration of the test, particularly in the first 30 minutes, leading to a decrease in overall subjective comfort. The analysis of pelvic motion yielded inconclusive findings for both genders. Based on these results, it is recommended that future tests should last at least 15 minutes per condition to obtain reliable and valid data.